Resistance to Abiotic Stress and Effectiveness of Native Rhizobia on Bambara Groundnut [Vigna subterranea (L.) Verdc.] in Benin - ZOUNDJI, Mahougnon Charlotte Carmelle; AHOGLE AGASSIN, Martinien Arcadius; AKPLO, Tobi Moriaque; GANGNON, Sèmèvo Armel Oslo; MONTEIRO, Diorel; Zanvo, K. A. Noël; KOUELO ALLADASSI, FÉLIX; HOUNGNANDAN, PASCAL (My University, 2022)
Bambara groundnut [ Vigna subterranea (L.) Verdc.], as a legume, can estab- lish relationships with nitrogen-fixing bacteria such as Rhizobium. However, Rhizobium efficacy is not always optimal due to the lack or poor efficient strains in the soil. This study aimed to evaluate symbiotic efficiency of endo- genous Rhizobia nodulating Bambara groundnut and their resistance to abi- otic conditions. Root nodules were randomly sampled from three agroeco- logical zones across the country, surface sterilized, ground and paste plated on YEMA media. After 24 hours, the bacterial colonies were purified. The pure cultures were further characterized using morphological and biochemi- cal methods and their resistance to antibiotics and heavy metals was eva- luated. Lastly, the symbiotic efficiency of the isolates was assessed through a greenhouse experiment. A total of eighty-five presumptive strains were iso- lated from Bambara groundnut roots nodules obtained from the farms. The physiological characterization of the isolated showed a decrease in isolates growth when NaCl concentration was more than 7%. In addition, 47% of the isolates were tolerant to a temperature of 40˚C. Most of the isolates were highly resistant to Erythromycin in all its concentration levels and to Kana- mycin, Spectinomycin, Neomycin and Ampicillin at 10 μg·mL−1 . Most of them showed resistance to Cu and Zn at 10 μg·mL−1 . Results of the effective- ness test on two Bambara groundnut varieties yielded dry shoot matter vary- ing from 3.33 g·plant −1 to 7.21 g·plant −1 for variety 1 and from 4.38 g·plant −1 to 8.38 g·plant−1 on variety 2. N uptake ranged between 0.09 g·plant−1 and 0.29 g·plant −1 for variety 1 and between 0.12 and 0.29 g·plant −1 for variety 2. The isolates yielding higher shoot dry weight and N uptake were LMSEM312, LMSEM338, LMSEM307, LMSEM351 for variety 1 and LMSEM338, LMSEM309, LMSEM307 for variety 2. The isolates showing better performance can be used to develop bio-fertilizer for sustainable Bambara groundnut production in Benin.
Keywords: Indigenous Rhizobia; Nitrogen Fixation; Biodiversity; Bambara Groundnut; West Africa